Effect of menstrual cycle on muscle strength and dynamic balance among recreational basketball players - Ler, Chai Hong (2022)
Background and Objective: Menstrual cycle is represented by a biological pattern formed by the cyclic variation of the endogenous sex hormones known as estrogen and progesterone. Different phases will have varies of hormones fluctuation thus the effect of the hormonal fluctuation might lead to sports injuries. This research is conducted to investigate the different across early and late follicular phase of menstrual cycle on muscle strength and dynamic balance among recreational basketball players. Methods: A total of 17 recreational basketball players (Age 21.05 ± 0.91years; Height 1.62 ± 0.05 m; Weight 53.42 ± 7.52 kg) with a self-reported regular menstrual cycle participated in this study. Their muscle strength and dynamic balance were measured on their day 1 and day 12 of menstruation. Muscle strength was measured by using Handheld Dynamometer (HHD). Dynamic balance was measured by using Y-Balance test. Results: The main finding were as follow: (1) there was no significant effect across early follicular phase as well as late follicular phase on participant’s muscle strength (p>0.05), (2) dynamic balance of participants shown a significant difference in late follicular phase compared to early follicular phase (p <0.05). Conclusion: This study reveals no significant different across early and late follicular phase of menstrual cycle on muscle strength but there was a significant different across early and late follicular phase of menstrual cycle on dynamic balance in dominant leg among recreational basketball players. This research would be advantageous for the recreational basketball player to take note of their poor balancing during the follicular phase. Balance training can be considered to avoid fall and lower extremity injuries.